RPG e história : o descobrimento do Brasil - Pereira, Priscilla Emmanuelle Formiga (2010)
This work - linked to the research line Teaching of History and Historical Knowledge, with a Concentration Area in Historical Culture - aim to discuss the role-playing game, also considered literature Interactive Role-Playing Games (RPG). Translated into our language as Jogo de Interpretação de Personagens, since its inception in the 70s in the United States by students Gary Gygax and Dave Arneson RPG went through several transformations, including marketing. In Brazil by means of a movement that seeks to improve the image of the hobby after alleged involvement in crimes, the game gained ground in the classroom as a methodological tool for teaching, including teaching of history. This work arose out of concern around the game assume the character of a teaching resource in the teaching of history, has as main source RPG written by Luiz Eduardo Ricon, O Descobrimento do Brasil, launched during the celebrations of 500 years of Brazil. Through an analysis of the references used by the author, our proposal fits in an attempt to characterize the type of product such as Historical Culture of the cultural industry builds from the moment that suggests a narrative about the Discovery and History of Brazil, bringing representations revolve around the very idea of national identity.